Potencial fisiológico de sementes de physalis angulata l. em função de fatores ecofisiológicos, promotores químicos e maturidade fisiológica - Santiago, Willen Ramos (2016)
The Physalis angulata L. is a species with potential for commercial cultivation, but it is still essentially a wild plant, in early process of domestication and with lack of information about its physiological and ecophysiological aspects, including those related to the germination of the seeds. The overall objective of this study was to evaluate the physiological potential of seeds of P. angulata L. due to ecophysiological factors, chemical promoters and physiological maturity. For this, three experimental tests were performed. In the first assay, we tested temperatures (25, 30, 35 °C), photoperiods (0, 8, 12 and 16 hours) and types of light (absence of light, white light, red light and far-red light. In the second assay, types and concentrations of chemical promoters were tested: gibberellic acid - GA3 (0.00, 0.02, 0.04, 0.06 and 0.08%), saltpetre - KNO3 (0.0; 0.2; 0.4; 0.6; 0.8 and 1.0%) and Stimulate® (0,0; 0,25; 0,50; 0,75; 1,00; 1,25; 1,50%). In the last sample, fruit and seeds of P. angulata L. were assessed for physiological maturation, according to the number of days after anthesis - DAA (7, 14, 21, 28 and 35 days). In all assays, germination and seed vigor tests were carried out in a completely randomized design. In general, the germination, the first germination count, germination speed index, seedling emergence in sand and length and seedling dry weight were quantified. In the second study, the diameter and mass of fruits, water content of the seeds, dry weight of 100 seeds, weight of thousand seed and electrical conductivity were also qualified. The P. angulata L. seeds expressed the highest physiological potential at a temperature of 35 °C and with no light, and they were adversely affected in function of the time of exposure to light during the germination. The three chemical promoters were effective in promoting increases in seed vigor and the concentrations of 0.06% of GA3, 0.4 to 0.6% of KNO3 and 1.0% of Stimulate® the most effective ones. In relation to the maturation, the seeds of P. angulata become physiologically viable from 21 DAA, with most physiological potential at 35 DAA. However, in order to avoid excessive fruit drop, due to senescence, it is recommended to perform the harvest after around 28 DAA